Oviposition Preference and Offspring Performance of Mechoris ursulus (Coleoptera: Attelabidae) in Cyclobalanopsis glaucoides (Fagales: Fagaceae) and Quercus franchetii (Fagales: Fagaceae) in Central Yunnan, China. Issue 1 (19th March 2015) - Wang, Xu; Hu, Shao-Ji; Zhang, Zhi-Ying; Geng, Yu-Peng; Bai, Xue
Abstract : Mechoris ursulus (Roelofs) (Coleoptera: Attelabidae) is a pest weevil of Fagaceae oak trees in eastern Asia. The female has a distinct branch-cutting behavior in conjunction with oviposition in the acorns of its host plant. This study analyzed the factors influencing oviposition preference by carrying out continuous field surveys over the course of 2009–2010 and through laboratory rearing. The field survey showed that for both of the hosts, Cyclobalanopsis glaucoides Schottky (Fagales: Fagaceae) and Quercus franchetii Skan, M. ursulus preferred branches with fewer acorns and larger acorns on the same branch for oviposition. Laboratory rearing experiments showed offspring performance (i.e., survival rate and fresh weight of larvae) was significantly and positively correlated with acorn size. Preference for larger acorns could maximize the fitness of offspring by providing sufficient food source and space.